Strategying continuous vocational training in digital economy - N. А. Simchenko; N. Yu. Anisimova (Вестник Северо-Кавказского федерального университета)
Introduction. The adoption of strategic decisions by the state authorities of the Russian Federation in the system of personnel training is formed in the conditions of digital instability, a shortage of qualified labor resources and an increase in sociotechnological inequality, which entails the need to form new approaches to their study. Goal. Scientific substantiation of the directions of strategizing continuous professional training in the digital economy. Materials and methods. The study is based on the analysis of the works of national and foreign scientists on the issues of strategic state planning of personnel training, methods for the formation of a state task for the provision of educational services in the Russian Federation, control figures for the admission of students and the needs of employers in personnel. The proposed approach makes it possible to take into account the actual dynamics of employment during the year, track industries with high seasonal fluctuations in the level of employment, and also take into account structural shifts in staffing needs caused by changes in the proportions in the national and regional economy. Results and discussion. The developed method of strategic state planning of continuous training of personnel was tested on the data of the regions of the Southern Federal District of the Russian Federation. On average, for all sectors of the economy of the Southern Federal District of the Russian Federation, the expected untapped potential of the continuous training system is 98.0%, which requires the adaptation of strategic state planning for training personnel to the conditions of digital transformation. Conclusion. Based on the results of the study, it can be concluded that the mechanisms of strategic state planning, formed on the forecasts for the development of the personnel training system, will create conditions for strengthening the personnel sovereignty of the Russian Federation and increase the sociocentricity of the digital economy.